Effects of relative low minute ventilation on cerebral haemodynamics in infants undergoing ventricular septal defect repair. (15th January 2020) - Zhang, Weizhi; Xie, Siyuan; Han, Ding; Huang, Jiapeng; Ou-Yang, Chuan; Lu, Jiakai
Abstract: Background: Ventilation-associated changes in blood carbon dioxide levels are associated with various physiological changes in infants undergoing surgery. Studies on the effects of mechanical ventilation on cerebral haemodynamics especially for infants with CHD are scarce. Aim: This study was done to compare the changes in regional cerebral oxygen saturation and cerebral blood flow velocity when the end-tidal carbon dioxide partial pressure changed during different minute ventilation settings in infants undergoing ventricular septal defect repair. Methods: A total of 67 patients less than 1 year old with ventricular septal defect were enrolled, and 65 patients (age: 6.7 ± 3.4 months, weight: 6.4 ± 1.5 kg) were studied. After anaesthesia induction and endotracheal intubation, the same mechanical ventilation mode (The fraction of inspired oxygen was 50%, and the inspiratory-to-expiratory ratio was 1:1.5.) was adopted. The end-tidal carbon dioxide partial pressure of 30 mmHg (T1), 35 mmHg (T2), 40 mmHg (T3), or 45 mmHg (T4) were obtained, respectively, by adjusting tidal volume and respiratory rate. Minute ventilation per kilogram was calculated by the formula: minute ventilation per kilogram = tidal volume * respiratory rate/kg. Regional cerebral oxygen saturation was monitored by real-time near-infrared spectroscopy. Cerebral blood flow velocity (systolic flow velocity, end-diastolic flow velocity, and mean flow velocity), pulsatility index, and resistance index were measured intermittently by transcranial Doppler. Systolic pressure, diastolic pressure, stroke volume index, and cardiac index were recorded using the pressure recording analytical method. Results: As the end-tidal carbon dioxide partial pressure increased from 30 to 45 mmHg, regional cerebral oxygen saturation increased significantly from 69 ± 5% to 79 ± 4% (p < 0.001). Cerebral blood flow velocity (systolic flow velocity, end-diastolic flow velocity, and mean flow velocity) increased linearly, while pulsatility index and resistance index decreased linearly from T1 (systolic flow velocity, 84 ± 19 cm/second; end-diastolic flow velocity, 14 ± 4 cm/second; mean flow velocity, 36 ± 10 cm/second; pulsatility index, 2.13 ± 0.59; resistance index, 0.84 ± 0.12) to T4 (systolic flow velocity, 113 ± 22 cm/second; end-diastolic flow velocity, 31 ± 6 cm/second; mean flow velocity, 58 ± 11 cm/second; pulsatility index, 1.44 ± 0.34; resistance index, 0.72 ± 0.07) (p < 0.001). There were significant differences in changes of systolic flow velocity, end-diastolic flow velocity, mean flow velocity, pulsatility index, and resistance index as the end-tidal carbon dioxide partial pressure increased from 30 to 45 mmHg between subgroups of infants ≤6 and infants >6 months, while the changes of regional cerebral oxygen saturation between subgroups were not statistically different. Regional cerebral oxygen saturation and cerebral blood flow velocity (systolic flow velocity, end-diastolic flow velocity, and mean flow velocity) were negatively correlated with minute ventilation per kilogram ( r = −0.538, r = −0.379, r = −0.504, r = −0.505, p < 0.001). Pulsatility index and resistance index were positively related to minute ventilation per kilogram ( r = 0.464, r = 0.439, p < 0.001). The diastolic pressure was significantly reduced from T1 (41 ± 7 mmHg) to T4 (37 ± 6 mmHg) (p < 0.001). There were no significant differences in systolic pressure, stroke volume index, and cardiac index with the change of end-tidal carbon dioxide partial pressure from T1 to T4 (p = 0.063, p = 0.382, p = 0.165, p > 0.05). Conclusion: A relative low minute ventilation strategy increases regional cerebral oxygen saturation and cerebral blood flow, which may improve cerebral oxygenation and brain perfusion in infants undergoing ventricular septal defect repair.